Organized networks of carbon nanotubes - Subramanian, K. R. V.; Rao, Aravinda Cl.; George, Raji. (Boca Raton : CRC Press, 2020)
In this book, meshes and networks formed out of multiwalled carbon nanotubes are investigated andanalyzed, including their use in niche applications such as electro-optic devices, advanced mechanical, thermal and electrical property enhancement, and gene editing. Different properties of multi-walled carbon nanotubes, including random network formation, ordering the meshes and networks by mechanical agitation and application of an external field, using crystallization and cross-linking induced phase separation in homopolymers-CNT composites are discussed with theoretical analysis. The book is aimed at researchers and graduate students in Electrical Engineering; Materials Science and Engineering; Chemical Engineering and Nanotechnology, Electronic circuit design, manufacturing, and characterization.
OCLC-licensed vendor bibliographic record.
Keywords: Carbon nanotubes; Electron transport; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / Circuits / General; TECHNOLOGY / Material Science